Pelatihan dan Pengembangan Sumber Daya Manusia Dalam Lembaga Pendidikan Islam - suci hartati; Nurul Hidayati Murtafiah (An Naba, 2022)
When Islamic educational institutions have low student achievement scores, teachers become the main target because they are considered ineffective, unimaginative, and boring. Therefore, it is widely believed that in order to meet this problem, Islamic educational institutions need access to higher quality human resources. This research is qualitative, in the form of a literature review. The main purpose of this study is to explain the basics, objectives, and phases of growth and training in Islamic educational institutions, as well as the criticality of practicing them. The human resources of Islamic educational institutions can be made more competent and professional through training, while development can motivate those already on staff to focus their ingenuity and initiative in new directions. Knowledge, problem solving skills, ability to foster morale, reduce stress and frustration, increase job satisfaction, independence and hard work, and ability to face modern challenges are all enhanced through planning, design, training, development and evaluation stages. Islamic educational institutions must conduct coaching and training efficiently if they want to produce superior educators and education.